2019
DOI: 10.2134/jeq2019.03.0147
|View full text |Cite
|
Sign up to set email alerts
|

Better Together: Water Treatment Residual and Poor‐Quality Compost Improves Sandy Soil Fertility

Abstract: Water treatment residual (WTR) is an underused clean water industry byproduct, generally disposed to landfill. This study assesses the benefits and risks of ferric-WTR as a soil amendment or co-amendment for plant growth in a nutrient-poor sandy soil. A 12-wk pot trial tested the efficacy of WTR and a locally available, low-quality, municipal compost as single (1, 5, and 12.5% dry mass) and co-amended treatments (1:1 WTR/compost ratio, at 2, 10, and 25%) on wheat (Triticum aestivum L.) growth in a sandy soil. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…However, compared to the control, the co-amendment of 10% Al-WTR, 10% C and P fertilizer resulted in higher maize growth and total biomass accumulation. This is in agreement with the work of Clarke et al (2019), which also found higher wheat biomass yield due to combined use of compost and WTR as a soil amendment compared with unamended soil. Similarly, Hsu and Hseu (2011) reported that co-application of compost and Al-WTR resulted in higher dry matter accumulation of Bahia grass (Paspalum notatum), although in their case, the resultant yield was not significantly different to sole Al-WTR treatments.…”
Section: Impact Of Al-wtr Use In Maize Productionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, compared to the control, the co-amendment of 10% Al-WTR, 10% C and P fertilizer resulted in higher maize growth and total biomass accumulation. This is in agreement with the work of Clarke et al (2019), which also found higher wheat biomass yield due to combined use of compost and WTR as a soil amendment compared with unamended soil. Similarly, Hsu and Hseu (2011) reported that co-application of compost and Al-WTR resulted in higher dry matter accumulation of Bahia grass (Paspalum notatum), although in their case, the resultant yield was not significantly different to sole Al-WTR treatments.…”
Section: Impact Of Al-wtr Use In Maize Productionsupporting
confidence: 93%
“…Alternatively, P fertilizer subsidies can be made available to farmers willing to incorporate Al-WTR in their farms. The higher N uptake due to the co-amendment in comparison with Al-WTR treatments reinforces the mutual benefits in nutrient supply when Al-WTR and compost are used together (Clarke et al, 2019). The surge in N uptake observed in the co-amendment due to the addition of fertilizer P was likely a result of an increase in P availability and thus improved root development which enabled the plants to take up more N from the soil.…”
Section: Influence Of Al-wtr Amendment On Plant Nutrient Uptakementioning
confidence: 55%
See 1 more Smart Citation
“…While the observed plant growth promotion effect could not be entirely attributed to one or another amendment, this latter study indicates that MSWC and WTR can be successfully used to increase crop yield in PTE-contaminated or degraded (i.e. nutrient poor) soils as also supported by other authors (Clarke et al, 2019;Hsu and Hseu, 2011;Zhao et al, 2016Zhao et al, , 2018.…”
Section: Water Treatment Residualssupporting
confidence: 73%
“…Tris/HCl is a common buffer used to extract metal-bound species from different genotypes of wheat [18 , 24] , probably for its lysis properties which can explain its high extraction ability. Ammonium nitrate is used as a fertilizer in agriculture to provide a source of nitrogen which stimulates the plant growth, and it was chosen because it was considered a suitable solvent to extract water-soluble plant available trace elements from soil [21 , 22] and toxic elements from contaminated grassland soils to assess metal mobility in soil [19] . It was expected ammonium nitrate to extract Zn-bound species better than Tris/HCl, because the ammonia [23] formed by its dissociation leads to the formation of soluble metal ammine complexes, mainly occurring in the soil, which are available for plants [19] .…”
Section: Extractionmentioning
confidence: 99%